Long‐term follow‐up of European APL 2000 trial, evaluating the role of cytarabine combined with ATRA and Daunorubicin in the treatment of nonelderly APL patients. Issue 7 (12th June 2013) - Adès, Lionel; Chevret, Sylvie; Raffoux, Emmanuel; Guerci‐Bresler, Agnes; Pigneux, Arnaud; Vey, Nobert; Lamy, Thierry; Huguet, Francoise; Vekhoff, Anne; Lambert, Jean‐Francois; Lioure, Bruno; de, Stephane; et al.
<x xml:space="preserve">Abstract</x> All‐trans retinoic acid (ATRA) combined to anthracycline‐based chemotherapy is the reference treatment of acute promyelocytic leukemia (APL). Whereas, in high‐risk patients, cytarabine (AraC) is often considered useful in combination with anthracycline to prevent relapse, its usefulness in standard‐risk APL is uncertain. In APL 2000 trial, patients with standard‐risk APL [i.e., with baseline white blood cell (WBC) count <10, 000/mm3] were randomized between treatment with ATRA with Daunorubicin (DNR) and AraC (AraC group) and ATRA with DNR but without AraC (no AraC group). All patients subsequently received combined maintenance treatment. The trial had been prematurely terminated due to significantly more relapses in the no AraC group (J Clin Oncol, (24) 2006, 5703–10), but follow‐up was still relatively short. With long‐term follow‐up (median 103 months), the 7‐year cumulative incidence of relapses was 28.6% in the no AraC group, compared to 12.9% in the AraC group (P = 0.0065). In standard‐risk APL, at least when the anthracycline used is DNR, avoiding AraC may lead to an increased risk of relapse suggesting that the need for AraC is regimen‐dependent. Am. J. Hematol. 88:556–559, 2013. © 2013 Wiley Periodicals, Inc.